New Regulatory Tariff Structure for Green Energy and Electric Vehicles in India - C. Verma, Mukesh; Ranjan, Rakesh; Kumar, Rakesh (International Journal of Engineering and Technology, 2018)
Electricity tariff is the price of electricity to be paid by the electricity consumers. Determination of electricity tariff is major function of the Regulatory Commissions of the concerned states. Tariff is analysed through a rational process including important role of all stakeholders, including electricity users. The regulator follows a set process mentioned in Act and Regulations, conducts public hearings before the tariff is determined. Special tariff rates need to be measured for Green Energy and Electric Vehicles (EVs) because of their sustainability in nature. State Electricity Regulatory Commissions (SERCs) have a major role to play in promoting Green Energy and EVs for providing optimum tariff structure for EV charging. Despite of new draft model regulations availability, progress is very slow. Regulators need to build a new cadre and capacity for making their regulations and policies to cater future needs. Time to implement new technology is less and utilities are only working on pilot projects. SERCs need to come forward to play leadership role for protecting an environment by promoting sustainability. In my paper, I would like to analyse current scenario and based on the global practice on various tariff structures to optimise electricity use and promote sustainability, will recommend new tariff structure.Â